There is no Such Thing as a Sham Trust - Li, BoHao (Victoria University of Wellington Law Review, 2023)
The Court of Appeal decision in Official Assignee v Wilson is the leading New Zealand case on "sham trusts". Obiter, O'Regan and Robertson JJ held that for a sham trust to exist, the settlor and trustee must have a common intention to not create a trust. Post-Wilson, debate continues over the precise elements that render a trust a sham. The Law Commission suggested that the sham doctrine, as a means of analysing the validity of an express trust, may not be the best approach. A better starting point would be a return to the certainty of intention requirement. In arguing that the Law Commission's recommendation is correct, this article will discuss three legal issues: whether an express trust is a unilateral or bilateral transaction; whether the excluded evidence has always been part of the objective intention requirement; and whether the legislative and policy factors have made foreign trust law distinct from New Zealand trust law. Finally, this article will expand on the test proposed by the Law Commission.